2003
DOI: 10.1007/s00572-002-0215-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arbuscular mycorrhizal fungi and a non-pathogenic Fusarium oxysporum on Meloidogyne incognita infestation of tomato

Abstract: Arbuscular mycorrhizal (AM) fungi and non-pathogenic strains of soil-borne pathogens have been shown to control plant parasitic nematodes. As AM fungi and non-pathogenic fungi improve plant health by different mechanisms, combination of two such partners with complementary mechanisms might increase overall control efficacy and, therefore, provide an environmentally safe alternative to nematicide application. Experiments were conducted to study possible interactions between the AM fungus Glomus coronatum and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 5 publications
4
25
0
1
Order By: Relevance
“…Nirenberg) reported by Hwang et al (1995). However, mycorrhizal suppression by Fusarium was not observed in Scots pine for L. deliciosus, in agreement with results obtained in other studies with F. oxysporum strains (García-Romera et al 1998;Diedhiou et al 2003).…”
Section: Discussionsupporting
confidence: 90%
“…Nirenberg) reported by Hwang et al (1995). However, mycorrhizal suppression by Fusarium was not observed in Scots pine for L. deliciosus, in agreement with results obtained in other studies with F. oxysporum strains (García-Romera et al 1998;Diedhiou et al 2003).…”
Section: Discussionsupporting
confidence: 90%
“…The increased shoot length in infested plants could be a temporal response of plants to M. incognita infestation which might be driven by the carbon drain due to the RKN infestation. Similarly shoot dry weight of tomato plants inoculated with M. incognita was increased at week 9 and was unaffected at week 12, while decreased shoot dry weight was only observed when tomato was infested with M. incognita after 15 weeks of growth (Diedhiou et al 2003). The significant decrease in root length in the present experiment implies that in the long term plants may suffer from RKN infection, as indicated by the higher root fresh weight in infested plants compared to non-RKN plants an indication of root damage due to gall formation (Table 3).…”
Section: Resultsmentioning
confidence: 94%
“…It has even been suggested that many root pathogens can be regarded as pathogens of mycorrhizae (Rhodes 1980), implying that AM fungi are closely associated with soil-borne pathogens, including nematodes (Graham 2001). Since AM fungi and RKN are all indigenous soil organisms and therefore co-exist in plant roots, the potential role of AM fungi as biocontrol agents and their protective effects on plants against RKN have been well documented Diedhiou et al 2003). Studies have shown that inoculation with AM fungi can significantly reduce RKN infestation and reproduction in some plant-nematode systems (Hol and Cook 2005) such as papaya with Meloidogyne incognita (Jaizme- Vega et al 2006), olive planting stocks with M. incognita and Meloidogyne javanica (Castillo et al 2006), tomato with M. incognita (Talavera et al 2001;Siddiqui and Akhtar 2007), pyrethrum with Meloidogyne hapla (Waceke et al 2001), Prunus rootstocks with M. javanica (Calvet et al 2001), and banana with M. javanica (Rodriguez and JaizmeVega 2005).…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, irrigation increased (Karajeh and Mohawesh 2016) and mycorrhizainoculation decreased (Diedhiou et al 2003) the number of Meloidogyne-induced galls on the roots. We did not experience these effects in our trial, probably due to the weather conditions of the year of the experiment.…”
Section: Resultsmentioning
confidence: 99%